Development of Learning Media Using Smart Apps Creator Application for Arabic Language Learning - Damulawan, Fira Sutira; Damhuri; Paputungan, Moh. Zulkifli (Language Development Center, 2023)
Background: The Arabic language teacher at Madrasah Tsanawiyah Al-Hikmah Mogutat Kotamobagu teaches Arabic using the KMA 183 textbook, a whiteboard, and an LCD projector. The teaching media employed by the teacher include illustrated paper and PowerPoint presentations. However, these methods have not yet increased students' interest, motivation, or learning outcomes in Arabic language lessons. Purpose: Based on interviews and an analysis of the Arabic language teacher's needs, the primary issue that requires immediate resolution is the presence of effective instructional media for the Arabic language subject. Method: This research follows the Research and Development (R&D) approach, using the ADDIE model. The development of instructional media, specifically using the Smart Apps Creator application, is tailored for students at MTs Al-Hikmah Mogutat Kotamobagu and is based on the Core Competencies (KI) and Basic Competencies (KD) of the Grade VIII Arabic language curriculum for Semester 1. Results and Discussion: The validation results from media experts for the developed instructional media show an average percentage score of 95.77%, which falls into the